2022
DOI: 10.1037/dev0001397
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents sample more information prior to decisions than adults when effort costs increase.

Abstract: Making better decisions typically requires obtaining information relevant to that decision. Adolescence is marked by increasing agency in decision-making and an accompanying increase in impulsive decisions, suggesting that one characteristic of adolescent decision-making is a tendency to make less-informed decisions. Adolescents could also be especially averse to the effort associated with acquiring relevant information to make decisions. To investigate this possibility, we recruited adolescents (M age = 15.02… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…A crucial difference between the current and previous studies is that previously, uncertainty was either description-based 45,72 , or required exploration or trial-and-error learning 45,[73][74][75] . Opposed to previous experiments, but like many situations in real-life 77 , our participants took risks under uncertainty but could not "look before they leap", and did not get instant feedback about the outcomes of their choice, eliminating confounds such as developmental differences in feedback processing or exploration.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…A crucial difference between the current and previous studies is that previously, uncertainty was either description-based 45,72 , or required exploration or trial-and-error learning 45,[73][74][75] . Opposed to previous experiments, but like many situations in real-life 77 , our participants took risks under uncertainty but could not "look before they leap", and did not get instant feedback about the outcomes of their choice, eliminating confounds such as developmental differences in feedback processing or exploration.…”
Section: Discussionmentioning
confidence: 76%
“…This is at odds with previous studies in which adolescents took more risks under uncertainty than adults 45,[72][73][74] . More recent research showed that adolescents require more information than adults before making a choice 75 , implying uncertainty aversion is a more complex phenomenon than previously thought. However, no earlier study could quantify the state of uncertainty their participants is in.…”
Section: Discussionmentioning
confidence: 93%
“…In line with these results, a later study found that adolescents are more accepting of uncertainty and ambiguity than children and adults, which was again related to self-reported real-life risk taking, whereas risk aversion declined monotonically over age and was not related to real-life risk taking ( van den Bos and Hertwig, 2017 ). These results suggest that the often observed increase in risk engagement in adolescents is due to an increased willingness to gamble when they lack complete knowledge, rather than increased risk-taking per se (but see Niebaum et al, 2022 ). This reduced ambiguity aversion might well be adaptive during adolescence, because adolescents relatively often find themselves in new, uncertain environments, in which behavior that promotes exploration can boost learning ( Ciranka and van den Bos, 2021a ).…”
Section: Informational Peer Influence In Adolescence: the Role Of Unc...mentioning
confidence: 85%
“…These weaker priors or more uncertain expectations in adolescents compared with adults might lead to further information seeking to resolve this uncertainty. A recent study found that, using an effort-based information sampling task, adolescents sampled more information than young adults before reaching a decision ( Niebaum et al, 2022 ). Taking this to the social domain by using a risky decision paradigm in which uncertainty and the presence of social information were manipulated, Ciranka and van den Bos found that young adults used the choices of others to a larger extent when they were more uncertain ( Ciranka and van den Bos, 2020 ).…”
Section: Informational Peer Influence In Adolescence: the Role Of Unc...mentioning
confidence: 99%
“…Search behavior for nonsocial information has been studied in adolescents using different types of experimental designs with mixed findings. The study of van den Bos and Hertwig (2017) suggests that adolescents search less for objective information compared with adults and children, while another recent study showed that adolescents searched more information compared with adults (Niebaum et al, 2022). In contrast, Somerville et al (2017) did not find quantitative differences in exploration behavior, but qualitative differences between adolescents and adults.…”
Section: Discussionmentioning
confidence: 99%